ANALISIS STRATEGI PENYEDIAAN PUPUK BERSUBSIDI BAGI PETANI DI KABUPATEN DEMAK PROVINSI JAWA TENGAH (Studi Pada Dinas Pertanian Kabupaten Demak) - Wiwik Dewi Sumbarwati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2016)
This research aims to define internal and external strategic factors, determine the component decisive strategic success and determine priority community assessment strategy related to the means of production which became one of the main needs of farmers Development in Demak. Research was done by the method of Purposive sampling.Collection of information using a questionnaire respondents, Focus Group Discussion (FGD) and in-depth interviews with key person. The purpose of the first and second study analyzed using SWOT (Strength Weakness-Opportunity-Threat) and the third goal is analyzed using AHP (Analitycal Herarchy Process). Based on the results of the SWOT analysis, weighting the interaction of internal and external factors obtained alternative strategy options with highest weights on a combination of Strength-Opportunity Strategies (SO). AHP analysis on starting with the preparation of model AHP hierarchy with the goal hierarchy “subsidized Fertilizer Strategy Analysis to the Farmers” is on a Level 1 assessment criteria is an alternative approach to the planning of the results of the Focus Group Discussion (FGD); Level 2 is the Alternative criteria for Subsidized Fertilizer Strategy Direction up to the farmers Development in Demak is SWOT Analysis Results SO.